Biological control of Septoria tritici blotch on wheat by Trichoderma spp. under field conditions in Argentina - Perelló, Analía Edith (2009)
Biological control is an additional tool available for the design of more sustainable control strategies of wheat diseases. Trichoderma spp. have previously been used as biocontrol agents to protect wheat plants against leaf spots diseases in Argentina, but the information from field assays is scarce. The effectiveness of four Trichoderma harzianum strains and one T. koningii strain in reducing the incidence and severity of the leaf blotching of wheat caused by Septoria tritici blotch (STB) under two formulation conditions, spore suspension and the coated-seed technique, was studied under field conditions. Significant differences between wheat cultivars, formulation types and growth stages were found. In 2003, at the tillering stage, all of the treatments tested (except SST1 for incidence) effectively reduced the incidence or the severity of the disease compared to the control. Similarly, in 2004, ten of the treatments reduced the severity at tillering. At the heading stage, none of the treatments tested caused a significant decrease of the disease. These results indicated, therefore, that the antagonism was effective at an early stage of the disease only. Comparing both formulations, spraying spore suspension onto leaves and the coated-seed application technique, both were effective in decreasing the disease. Some isolates, such as CST4 and CST2, reduced the incidence value of STB to 40% and the severity value to 70% of the control values applied as coated-seed formulation. On the other hand, isolates T4 and T2 showed the greatest effectiveness for controlling STB, with similar reduction values to that shown by the fungicide (Folicur®) application treatment. The results of this study indicated that, although the immediate impact of Trichoderma isolates may be seen as reduced incidence and severity on the first stages of STB, in the long term, the same disease levels as found in untreated sites may be attained. This study also demonstrated that the incorporation of Trichoderma as a biocontrol preparation may be a promising step towards reducing STB disease in the field and the levels of fungicide residues in the context of a more integrated approach to the problem.